Students’ Mathematical Problem-Solving Ability in Solving Quadratic Function Problems - Yusuf Devan Nr; Lilis Marina Angraini; Astri Wahyuni; Putri Wahyuni (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Problem-solving ability is a central component of mathematics learning because it enables students to understand problems, develop solution strategies, implement mathematical procedures, and evaluate the correctness of their answers. This study aimed to describe Grade 10 students’ mathematical problem-solving ability in solving quadratic function problems. A descriptive quantitative design supported by follow-up interviews was employed. The participants were 34 students from Class X.2 of SMA Negeri 3 Tualang. Data were collected through a mathematical problem-solving test and semi-structured interviews with six students selected to represent high, medium, and low levels of problem-solving ability. The test scores were categorized into three levels, and the interview data were used to clarify students’ solution processes. The findings showed that two students were classified in the high category with scores above 34.51, 25 students were classified in the medium category with scores ranging from 15.79 to 34.51, and four students were classified in the low category with scores below 15.79. Overall, students’ mathematical problem-solving ability in quadratic functions was categorized as medium. The interview results indicated that students mainly experienced difficulties in planning solution strategies and checking the correctness of their answers.